Vision, Perspectivism, and Haptic Realism. Issue 5 (December 2016) - Chirimuuta, M.
Abstract : In this article I examine the perceptual metaphor at the heart of perspectivism, discussing three elements: partiality, interestedness, and interaction. I argue that perspectivists should drop the visual metaphor in favor of a haptic one. Because the sense of touch requires contact and purposeful exploration on the part of the perceiver, it is obvious that with touch one apprehends an extradermal reality in virtue of and not in spite of its interactive and interested nature. By analogy, perspectivists should investigate the thesis that scientific representations inform us about the natural world in virtue of their interactive and interested qualities.